Inhibition By Toxic Compounds In The Hemicellulosic Hydrolysates On The Activity Of Xylose Reductase From Candida Tropicalis - M. Rafiqul, Islam; Mimi Sakinah, A. M.; Zularisam, A. W. (Springer Netherlands, 2014)
Xylose reductase (XR) is an oxidoreductase having potential applications in the production of various specialty products, mainly xylitol. It is important to screen for compounds that can decrease XR activity and consequently can decrease xylitol production. We have identified the byproducts in the hemicellulosic hydrolysate that inhibit XR from Candida tropicalis and measured their effects. XR inhibitory activities of byproducts, glucose, acetic acid, arabinose, lignin-degradation products (LDPs), furfural and hydroxymethylfurfural (HMF), were evaluated by measuring the MIC and IC50 values. XR activity was 11.2 U/ml. Acetic acid, LDPs, furfural and HMF significantly inhibited XR with IC50 values of 11, 6.4, 2.3 and 0.4 g/l, respectively. This is the first report on the inhibitory activities of several byproducts for XR.